Outcomes and risk factors of postoperative hepatic dysfunction in patients undergoing acute type A aortic dissection surgery - Zhou, Wei; Wang, Guokun; Liu, Yaoyang; Tao, Yun; Du, Zhen; Tang, Yangfeng; Qiao, Fan; Liu, Yang; Xu, Zhiyun (Journal of Thoracic Disease, 2019)
Background: Postoperative hepatic dysfunction (HD) increases the morbidity and mortality risk after cardiac surgery; however, only a few studies have specifically focused on acute type A aortic dissection (AAAD) surgery. We explored the possible risk factors and outcomes of early postoperative HD in patients with AAAD undergoing surgery. Methods: All patients who underwent AAAD surgery at our institution from April 2015 to April 2017 were retrospectively evaluated. Postoperative model for end-stage liver disease (MELD) score was used to define HD. Independent risk factors for HD were determined by multivariate logistic analysis. Results: Two hundred fifteen patients with AAAD met the inclusion criteria. The incidence rate of early postoperative HD was 60.9%, and the rate of in-hospital mortality was 16.8%. Patients with a high postoperative MELD score had longer mechanical ventilation time, longer durations of intensive care unit (ICU) stay, and higher in-hospital mortality. During the postoperative period, patients with AAAD complicated by HD needed continuous renal replacement therapy (CRRT), reintubation, tracheostomy, and blood transfusion more frequently. Aortic cross clamp (ACC) time [per 10 min higher; odds ratio (OR): 1.216, 95% confidence interval (CI): 1.017–1.454, P=0.032], postoperative leucocytes (per 2×109/L higher; OR: 1.161, 95% CI: 1.018–1.324, P=0.026), postoperative respiratory dysfunction (OR: 3.176, 95% CI: 1.293–7.803, P=0.012), and postoperative low cardiac output syndrome (LCOS) (OR: 12.663, 95% CI: 1.432–111.998, P=0.022) were independent risk factors associated with HD in patients undergoing AAAD surgery. Conclusions: Postoperative HD prolongs mechanical ventilation time and ICU stay, and is associated with increased in-hospital mortality among patients who undergo AAAD surgery. Several factors are associated with a high postoperative MELD score.